PENGARUH KEPEMILIKAN INSTITUSIONAL DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI: Studi Empiris Pada Perusahaan Manufaktur Sektor Property dan Real Estate Yang Terdaftar di BEI - Nisa Aulia; Desy Purwasih (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to prove empirically the effect of institutional ownership and capital intensity on tax avoidance with firm size as a moderating variable. The independent variables used in this study are institutional ownership and capital intensity, while the dependent variable is tax avoidance. This study also uses a moderating variable in the form of company size. The population in this study are property and real estate manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sample selection method used purposive sampling, based on this method, 12 companies were obtained. The data used in this study is secondary data in the form of annual financial reports. Based on the results of the study indicate that institutional ownership and capital intensity simultaneously affect tax avoidance. Institutional ownership has no effect on tax avoidance. Capital intensity has a negative effect on tax avoidance. Firm size is not able to moderate the effect of institutional ownership on tax avoidance. Firm size is not able to moderate the effect of capital intensity on tax avoidance.moderate the effect of capital intensity on tax avoidance